Comparison of electromagnetic exposures from the positioning antenna of driverless vehicle in adult and child passengers - Dong, Xuwei; Ren, Yufei; Lu, Mai (Archives of Electrical Engineering, 2026)
With the rapid development of driverless systems technologies, the differences in electromagnetic exposure levels amongst passengers of different ages have become a research hotspot in this field. This study focuses on the electromagnetic exposure of adults and children inside an electric vehicle caused by positioning antennas of driverless systems. Based on the COMSOL Multiphysics software, an electromagnetic numerical calculation model is established, including a vehicle body model, an antenna model, and separate models for an adult and child. Considering the differences in body size and dielectric properties between adults and children, the finite element method is used to calculate exposure levels under the electromagnetic environment generated by the positioning antenna. The results reveal that the electromagnetic exposure level in a child’s body is higher than that in an adult due to the former’s smaller body size and higher dielectric parameters. This study facilitates the evaluation of the electromagnetic environment of positioning antennas in electric vehicle driverless systems, provides a basis for improving electromagnetic radiation safety standards inside electric vehicles, and promotes the rapid development of electric driverless technologies while ensuring public health and safety.